Polypharmacy problems in geriatric practice of Kyrgyz Republic - A. T. Sharaeva; A. A. Zurdinova (Izdatelstvo OKI, 2022)
World statistics shows increasing numbers of aging population and increasing number of patients with multiple comorbidities, i. e. polymorbidity, which today is an urgent problem of modern clinical geriatric practice. During clinical examination of elderly and senile patients, at least 4-5 diseases and manifestations of pathological processes are diagnosed on the average. Because of this many medicines are prescribed to elderly patients at the same time, unfortunately, often unreasonably, which becomes a widespread phenomenon and is called polypharmacy. Polypharmacy is associated with an increased risk of adverse reactions that can lead to hospitalization or even death, as well as a significant increase in health care costs.In this regard, an analysis of medication prescribing in elderly inpatients with cardiovascular disease using the Medication Rationality Index (MAI) was conducted. As a result, it was found that professionals who provide care to patients are not sufficiently aware of the peculiarities of the use of drugs in elderly patients and in our health care sector there are no regulatory documents on the care of elderly patients.